1984
DOI: 10.1002/pssb.2221240144
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of the Total Mobility in a One‐Band Model Applicationto n‐Type MoTe2

Abstract: Une Btude comparative, dans un modble it une bande, de l'expression de la mobilite totale des porteurs, d6duite de la formule de Debye-Conwell et de la rbgle de Mathiessen, est proposke. Nous donnons la variation resultante de la mobilitk et du terme cinktique du pouvoir thermoBlectrique. Les rBsultats expirimentaux de conductivitB Blectrique de pouvoir thermoB1ectriqu.e obtenus sur MoTe, monocristallin sont expliquBs par un modhle classique de semiconducteur compensk. Nous montrons que l'application de la rbg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 8 publications
1
13
1
Order By: Relevance
“…were p-type [l] while those prepared by the vapour transport method with bromine as transport agent were n-type [6]. Therefore the idea used in this work was to anneal under bromine atmosphere a p-type single crystal to obtain a p-n junction.…”
Section: Methodssupporting
confidence: 64%
“…were p-type [l] while those prepared by the vapour transport method with bromine as transport agent were n-type [6]. Therefore the idea used in this work was to anneal under bromine atmosphere a p-type single crystal to obtain a p-n junction.…”
Section: Methodssupporting
confidence: 64%
“…According to the conventional equation μ = ( L / W )( d / ε 0 ε r V ds )(Δ I ds /Δ V bg ), where μ is the field‐effect mobility, L / W is the channel length‐to‐width ratio and is 1 for this study, ε 0 is the permittivity in vacuum, ε r is 3.9 for SiO 2 , and d is the thickness of the dielectric layer (285 nm), we obtained mobilities of 0.03 and 0.30 cm 2 V −1 s −1 , extracted at V ds = 10 V in the high V bg region, for electrons and holes, respectively. Both mobilities were much lower than the theoretical prediction in the literature, implying the existence of a large contact resistance in the layered MoTe 2 transistors.…”
contrasting
confidence: 56%
“…Other distinctive properties have also been addressed in bulk MoTe 2 . Its mobility at room temperature (RT), for example, can theoretically reach up to 200 cm 2 V −1 s −1 . Both p‐ and n‐type materials were synthesized through controlling the growth conditions in MoTe 2 crystals, leading to their use in light‐emitting transistors (p–n junctions) .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that the theoretical value of carrier mobility in bulk hexagonal (2H) MoTe 2 could be up to 200 cm 2 V 1 s 1 . 9 After the formation of few-layered compounds, people always hope a significant increase of carrier mobility by orders of magnitude just like other layered materials. 10 However, the currently reported mobility of few-layer 2H-MoTe 2 in adjustable bipolar transistor is less than 1 cm 2 V 1 s 1 .…”
Section: Introductionmentioning
confidence: 99%